Structure and thermoelectric properties of the n-type clathrate Ba8Cu5.1Ge40.2Sn0.71. Issue 37 (7th October 2015) - Xu, Jingtao; Wu, Jiazhen; Shao, Hezhu; Heguri, Satoshi; Tanabe, Yoichi; Liu, Yongfu; Liu, Guo-Qiang; Jiang, Jun; Jiang, Haochuan; Tanigaki, Katsumi
<x xml:space="preserve">Abstract</x> We study type I clathrate Ba8Cu5.1Ge40.2Sn0.7 single crystals (space group Pm3̄n, no. 223, a = 10.7151(3)) grown using a Sn flux method, and the thermoelectric figure of merit ZT of single crystals reaches a maximum value of 0.6 at 773 K.